The Relevance of Adopting Proofreading Tools to Maintain Academic Writing Integrity and Coherence Text - Dwi Astuti Wahyu Nurhayati (Indonesian Journal of EFL and Linguistics, 2022)
This study boasted some authors’ and editorial teams’ perspectives on academic integrity and adopting coherence properties, then using some Internet-based programs such as Mendeley, Grammar Checker, Turnitin, and coherence properties are considered as media options for 95 academicians such as authors, lecturers, even students, to produce acceptable works. With the correct and honesty of scientific works, then validity can be ensured. The data were figured out by adopting a descriptive qualitative design and compiled in consideration of 4 months, beginning from arranging pre-survey and post-survey in January to April 2022. The findings affirmed that Turnitin has many benefits to check sentences that consist of plagiarism, mark with different colors, and detect the source of website and copy-paste; to check plagiarism on the students’ tasks such as thesis, homework, article, and Mendeley presents some advantages to create a citation and reference manager used by the study and academician in citing references, especially from journals; to help them create bibliography and cite what they wrote; and to collect, arrange, share, and use the references related researches. Then Grammar Checker also provides some advantages, namely to check spelling, punctuation, and grammar structure automatically; to check the mistakes such as run-on sentences, accuracy, and consistency of the text. They employed the coherence pattern of deductive and inductive paragraphs containing complete elements of the claim, support, and warrant, including several strategies; definition strategy, comparative strategy, cause-effect, problem-solution strategy, means-end, listing, and partiting strategy. The results highlight that creating appropriate, standard scientific publications, adopting applicable coherence properties and contextual academic publishing were the requirements of an academician.